2004
DOI: 10.1101/gad.1239004
|View full text |Cite
|
Sign up to set email alerts
|

Dosage-sensitive requirement for mouse Dll4 in artery development

Abstract: Involvement of the Notch signaling pathway in vascular development has been demonstrated by both gain-and loss-of-function mutations in humans, mice, and zebrafish. In zebrafish, Notch signaling is required for arterial identity by suppressing the venous fate in developing artery cells. In mice, the Notch4 receptor and the Delta-like 4 (Dll4) ligand are specifically expressed in arterial endothelial cells, suggesting a similar role. Here we show that the Dll4 ligand alone is required in a dosage-sensitive mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
502
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(533 citation statements)
references
References 16 publications
25
502
2
4
Order By: Relevance
“…Of the Notch receptors, the loss of Notch1 proved to be the most deleterious to vascular development (Conlon et al, 1995;Krebs et al, 2000;Swiatek et al, 1994). Furthermore, several studies have demonstrated expression of Notch receptors and ligands in blood vessels and mural cells (Alva and Iruela-Arispe, 2004;Benedito and Duarte, 2005;Claxton and Fruttiger, 2004;Duarte et al, 2004;Gale et al, 2004;Shutter et al, 2000;Villa et al, 2001). These studies have also generally agreed that in addition to capillaries, Notch ligands and receptors are mostly confined to arteries, a finding that was subsequently supported by the requirement of Notch in establishing arterial identity through expression of EphrinB2 (Lawson et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the Notch receptors, the loss of Notch1 proved to be the most deleterious to vascular development (Conlon et al, 1995;Krebs et al, 2000;Swiatek et al, 1994). Furthermore, several studies have demonstrated expression of Notch receptors and ligands in blood vessels and mural cells (Alva and Iruela-Arispe, 2004;Benedito and Duarte, 2005;Claxton and Fruttiger, 2004;Duarte et al, 2004;Gale et al, 2004;Shutter et al, 2000;Villa et al, 2001). These studies have also generally agreed that in addition to capillaries, Notch ligands and receptors are mostly confined to arteries, a finding that was subsequently supported by the requirement of Notch in establishing arterial identity through expression of EphrinB2 (Lawson et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the ligands, only the loss of either Jag1 or Dll4 results in vascular defects, indicating that the other three Notch DSL ligands may not be as involved in vessel development. Notably, analysis of the phenotypes exhibited by Jag1 (Xue et al, 1999) and Dll4 (Duarte et al, 2004;Gale et al, 2004;Krebs et al, 2004) knockout mice, suggested that these two ligands are not functionally redundant. Indeed, the onset of lethality would indicate that each one of these molecules might provide a different array of signals through activation of Notch receptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cell-specific gain-of-function mutation of b-catenin in mice results in upregulation of Notch signaling, thereby altering vascular remodeling during embryonic development (36). Particularly, b-catenin stabilization in endothelial cells increases DLL4 transcription, leading to vascular phenotypes resembling those produced by DLL4 overexpression, including endothelial cell arterialization, lack of vascular remodeling, defects in branching, and loss of venous identity (39) …”
Section: Canonical Wnt Signaling In Vascular Endothelial Cellsmentioning
confidence: 99%
“…Jag2 is expressed in OFT myocardium from E11.5-E15.5 [149]. Of the Dll ligands, only Dll4 is expressed in the developing heart within the cardiac crescent, endocardium (after E8.5) and ventricular endocardium after E11.5 [150,151]. The Notch targets, Hey1 and Hey2 are expressed in the heart tube, endocardium (Hey2 specifically in the AVC and OFT endocardium at E11) and atrial (Hey1) and ventricular (Hey2) myocardium at E10.5 [152,144].…”
Section: Notch Signalling In Cardiac Valve Developmentmentioning
confidence: 99%